Monitoring of cyanobacterial blooms and assessing polymer-enhanced microfiltration and ultrafiltration for microcystin removal in an Italian drinking water treatment plant. (1st October 2021) - Akyol, Çağrı; Ozbayram, E. Gozde; Accoroni, Stefano; Radini, Serena; Eusebi, Anna Laura; Gorbi, Stefania; Vignaroli, Carla; Bacchiocchi, Simone; Campacci, Debora; Gigli, Fabiola; Farina, Giuseppe; Albay, Meric; et al.
Abstract: The water intake of a drinking water treatment plant (DWTP) in Central Italy was monitored over six bloom seasons for cyanotoxin severity, which supplies drinking water from an oligo-mesotrophic lake with microcystin levels up to 10.3 μg/L. The historical data showed that the water temperature did not show extreme/large seasonal variation and it was not correlated either with cyanobacterial growth or microcystin concentration. Among all parameters, the cyanobacteria growth was negatively correlated with humidity and manganese and positively correlated with atmospheric temperature. No significant correlation was found between microcystin concentration and the climatic parameters. Polymer(chitosan)-enhanced microfiltration (PEMF) and ultrafiltration (PEUF) were further tested as an alternative microcystin removal approach from dense cyanobacteria-rich flows. The dominant cyanobacteria in the water intake, Planktothrix rubescens, was isolated and enriched to simulate cyanobacterial blooms in the lake. The PEMF and PEUF were separately applied to enriched P. rubescens culture (PC) (microcystin = 1.236 μg/L) as well as to the sand filter backwash water (SFBW) of the DWTP where microcystin concentration was higher than 12 μg/L. The overall microcystin removal rates from the final effluent of PC (always <0.15 μg/L) were between 90.1-94.7% and 89.5–95.4% using 4 and 20 mg chitosan/L, respectively. Meanwhile, after the PEMF and PEUF of SFBW, the final effluent contained only 0.099 and 0.057 μg microcystin/L with an overall removal >99%. The presented results are the first from the application of chitosan to remove P. rubescens as well as the implementation of PEMF and PEUF on SFBW to remove cyanobacterial cells and associated toxins. Graphical abstract: Image 1 Highlights: Monitoring of an Italian DWTP over six bloom seasons for cyanotoxin severity. Unconventional water quality correlations were found with bloom events. Sand filter backwash water (SFBW) was critical for cyanotoxin accumulation. First time reporting of PEMF and PEUF on SFBW to remove cyanobacteria/toxins. PEUF showed great microcystin removal efficiencies (>99%) in the SFBW effluent.